Mechanical behavior of spiral reinforcement recycled aggregate concrete round columns under axial compression after spraying water at high temperatures - Wang, Xin; Li, Junya; Huang, Leiqun; Xie, Wangjun; Chen, Zongping (Frontiers in Materials, 2022)
Spiral hoops can effectively enhance the load-bearing capacity of recycled aggregate concrete columns, and the mechanical performance of such a member after experiencing fire and a fire sprinkler is very important for its application and promotion. Aiming at this problem, the mechanical behavior of spiral reinforcement recycled aggregate concrete round columns under axial compression after spraying water at high temperatures cooling was investigated. Three parameters including recycled coarse aggregate replacement ratio, temperature, and pitch of screw stirrups were taken into consideration. 26 specimens were designed for static loading test. The failure modes of regenerated concrete columns with spiral reinforcement were observed after cooling by high-temperature water spraying. The mechanical properties of specimens under different cooling modes after high temperatures were obtained and analyzed. The results indicate that the effect of the recycled aggregate replacement ratio on the performance of the specimens was mainly in terms of peak displacement. And the reduction in the spiral stirrup spacing increases the peak load and ductility coefficient of the specimens. The high temperature above 600°C has a obvious effect on the mechanical properties of the specimens. Water spray cooling can reduce the appearance of small cracks on the surface of the specimens and their peak displacement. The calculation method of bearing capacity of regenerated spiral reinforced concrete columns cooled by high-temperature water spraying was discussed.